Perbandingan Hot-deck, SVM, dan Random Forest dalam Mengidentifikasi Industri Mikro dan Kecil Terdampak Covid-19 Tahun 2020 - Iman Jihad Fadillah; Lalu Moh. Arsal Fadila; Lalu Muhamad Winadi Darundiye (Seminar Nasional Official Statistics, 2022)
The spread of Covid-19 has been declared a pandemic since March 2020. The pandemic coupled with policies by the government resulted in a decline in the economic sector, especially in micro and small industries (IMK). Identifying IMK affected by the Covid-19 pandemic is an important step. There are two types of identification methods that are commonly used, namely statistical-based methods and machine learning-based methods. Each method has different measurement results. Therefore, an appropriate method is needed to identify IMKs affected by the Covid-19 pandemic. This study aims to compare the hot-deck, SVM and random forest methods, in order to obtain the best method to identify IMK affected by Covid-19. The results obtained are that the random forest method is the best method in identifying IMK affected by Covid-19.